Analysis Of The Process For Preparing The Treasurer's Expenditure Accountability Report At The Sikur District Office - Hidayatul Akma (Cita konsultindo, 2024)
The importance of efficient financial management in local government institutions, including sub-district offices, has become the focus of attention in efforts to improve public services and appropriate use of resources. In this context, preparing the treasurer's accountability report for expenditure is a crucial step to ensure transparency, accountability and compliance with applicable regulations. This research aims to analyze the process of preparing the expenditure treasurer's accountability report at the Sikur District office based on Minister of Home Affairs Regulation Number 55 of 2008 and Minister of Home Affairs Regulation Number 77 of 2020 as well as identifying the obstacles faced in the process of preparing the administration and expenditure treasurer's accountability report. The research method used is a qualitative method. Data was collected by observation, interviews and documentation and analyzed using descriptive methods. The results of the research show that the process of preparing the administration and preparing the accountability report for the expenditure treasurer at the Sikur District Office is in accordance with applicable regulations. Human resources as well as facilities and infrastructure can support the administration process and preparation of the treasurer's accountability report for expenditure.